Integrasi Isu Sosioscientifik dalam Pendidikan Sains untuk Meningkatkan Keterampilan Argumentasi Ilmiah: Tinjauan Sistematis - Desilawati Triana; Muhamad Yusup; Ida Sriyanti (Postgraduate, University of Mataram, 2026)
Socioscientific Issues (SSI) integration in science education connects scientific concepts with complex real-world problems while fostering students’ scientific argumentation skills. This systematic review examines SSI integration in science learning, its contribution to students’ scientific argumentation, and the role of digital learning resources.The review followed PRISMA 2020 guidelines and analyzed empirical studies published between 2020 and 2025. Literature searches were conducted in October 2025 using Scopus, ScienceDirect, and Taylor & Francis Online with Boolean operators such as (“socioscientific issues” AND “scientific argumentation”). From an initial pool of 800 articles, 36 studies met the inclusion criteria and were analyzed through thematic synthesis. The findings reveal four dominant SSI integration patterns: scientific discuSSIon and debate, problem- and project-based learning, evidence-based decision-making, and digital instructional media. SSI integration consistently strengthens structural and dialogic argumentation, evidence evaluation, complexity-based reasoning, and consideration of ethical and social dimensions. However, studies integrating SSI into digital instructional resources remain limited. Teacher competence, argumentative scaffolding, and contextual issue relevance were identified as key supporting factors, while limited instructional materials and curriculum pressure became major barriers. These findings provide an empirical foundation for developing SSI-based science instruction and digital learning resources that support scientific argumentation in 21st-century education.